Intra-systemic Translations in Children’s Literature (1940-1980) - Domínguez Pérez, Mónica (Madrygal. Revista de Estudios Gallegos, 2015)
According to the polysystem theory, intra-systemic translations are those produced, distributed and consumed inside the same polysystem as its source text. In this paper we will analyse several examples of possible intra-systemic translations, all of which belong to children’s literature inside the Spanish domain during the period between 1940 and 1980. Special atention will be paid to Felipito y sus travesuras, book translated from Galician to Castilian Spanish.